Efficiency Analysis of Ripple Mill Capacity 6 Ton/Hours on Maintenance Machine - Siregar, Ahdiat Leksi; Zulfiah, Riyansa Devi; Rahardja, Istianto Budhi; Rantawi, Azhar Basyir; Saputera, Hendra (Journal of Applied Sciences and Advanced Technology, 2023)
Ripple mill is a machine used to crush palm kernels at the nut kernel station. This research aims to find out how the ripple mill machine works and determine the relationship between machine maintenance carried out on the performance efficiency of the ripple mill. The working principle of a ripple mill is that palm kernels that are fed into the ripple mill will be ground and crushed between the rotor and stator with an engine speed of 1200 rpm. The components contained in the ripple mill are the rotor bar which consists of 40 bars arranged in a circle, the stator bar consists of 18 bars at the front and 18 bars at the back, the v-belt pulley used is of the type B65 and B67 according to the position of the motor, then the flange bearing is used as a position for the shaft on the rotor before connecting to the pulley. Based on the results of research that has been carried out, it was found that the feed entering the ripple mill is 5.6 tons / hour with an installed capacity of 6 tons / hour. The working hours that have been set for the ripple mill are 300 operating hours, after observations it was obtained that it was 320 operating hours with the efficiency results obtained remaining in accordance with the predetermined standards, namely 95% - 99%.